Ancestral Religions and The Grand Narrative of Official Religions in Indonesia: A Postmodernist Analysis - Rahman, Eka Yuliana; Lasido, Nur Allan; Syawie, Hanief (Institut Agama Islam Negeri (IAIN) Manado, 2024)
This research presents an updated analysis of the dynamics of ancestral religion in Indonesia using a postmodernist approach. This research aims to review how ancestral religions are understood within the grand narrative of official religions and the implications for the division of rights and treatment of citizens based on religious choices, which often become political issues. Through a qualitative approach and analysis of postmodernism popularised by Lyotard and Foucault, this research dismantles the single narrative of official religions. The method used is critical discourse analysis. The main findings of this research show that ancestral religions in Indonesia face pressure from the grand narratives of official religions. Ancestral religions are often positioned as part of problematic activities that result in not getting equal recognition with official religions. On the other hand, the grand narrative of official religion impacts the meaning and interpretation of ancestral religions that are still considered sinful, and there are still restrictions on their religious practices. The implications of the findings of this research point to the political and social aspects of categorising ancestral religions as